Reflections on Social Life in Novel Re and Perempuan: A Sociological Analysis of Literature - Elvina Anjarini (JOURNAL OF SOCIETY INNOVATION AND DEVELOPMENT, 2023)
This research aims to reflect and describe the social life of a lesbian prostitute or commonly called a prostitute in Maman Suherman's novel Re and Perempuan using Alan Swingewood's theory of literary sociology and the role of literary sociology itself. In this research the author used descriptive analytical methods in researching existing problems. The data sources used are the novel by Maman Suherman entitled Re and Perempuan, research journals and other reference sources. The results of data analysis show that there is an analysis of the main characters: Re, Symbol of Hope and Change, Themes of Suffering and Redemption, and the Role of Literary Sociology in Social Reflection in the novels studied. This research also succeeded in revealing deep social reflections in a literary context through the life story of Re, a commercial sex worker, and her daughter Melur, depicting complex social realities, especially in the context of marginalization, identity and social struggle.